2009
DOI: 10.1007/s11431-009-0090-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal cracking of aviation kerosene for scramjet applications

Abstract: Thermal cracking of China No.3 aviation kerosene was studied experimentally and analytically under supercritical conditions relevant to regenerative cooling system for Mach-6 scramjet applications. A two-stage heated tube system with cracked products collection/analysis was used and it can achieve a fuel temperature range of 700-1100 K, a pressure range of 3.5-4.5 MPa and a residence time of approximately 0.5-1.3 s. Compositions of the cracked gaseous products and mass flow rate of the kerosene flow at varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…The fuel mass flow rate was calibrated and measured using a fuel collection system. Details of the fuel heating, control and collection system were described in our previous work [6,7,12].…”
Section: Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…The fuel mass flow rate was calibrated and measured using a fuel collection system. Details of the fuel heating, control and collection system were described in our previous work [6,7,12].…”
Section: Experimental Set-upmentioning
confidence: 99%
“…During fuel injection, the supercritical fuel can be directly transformed to the gaseous state without atomization and vaporization processes. When the fuel temperature is sufficiently high, the fuel pyrolysis occurs as well [7]. Experimental results [6,8] demonstrated that the overall burning intensity as well as the combustion efficiency improved with supercritical/cracked kerosene injection.…”
mentioning
confidence: 97%
“…The one-dimensional mass, momentum and energy equation with a 10-species surrogate for China No.3 aviation kerosene [3,7] are solved to obtained the flow properties of the kerosene along the cooling path. The convective heat transfer of the coolant is determined with correlation formulas based on the experimental results of heated kerosene flow at supercritical pressures [7,9] . The 3-dimensonal heat conduction equation is solved to obtain the distribution of wall temperature and heat flux of the strut with cooling effect.…”
Section: Fluid/solid Heat Transfer Couplingmentioning
confidence: 99%
“…Instead of real EF, the model uses some fictitious substance that decomposes without any intermediate reactions (so-called one-step pyrolytic mechanism) [5,6]. Empirical constants and functions described the fictitious substance decomposition are chosen for obtaining good agreement between computed and experimental data for real EF [7,8].…”
Section: Introductionmentioning
confidence: 99%